Program to Promote the Health of the Elderly in Kalasin Province Using Traditional Music and Dramatic Arts - Janchuay, Praewpannee; Pathomvanichkul, Wimonmas; Worakham, Paisarn (Journal for Developing the Social and Community, 2024)
The purposes of this research were to : (1) Study the needs and current conditions regarding the health of the elderly in Kalasin Province. (2) Develop a program to promote the health of the elderly in kalasin province using traditional music and dramatic arts. and (3) Study the results of testing of the program to promote the health of the elderly in kalasin province using traditional music and dramatic arts. Target groups were a group of 30 elderly people in the elderly school, Namon subdistrict municipality, Obtained through purposive sampling. The tools used were questionnaires, behavioral observation form and assessment form. The statistics used were percentage, mean, standard deviation. The research results were found : (1) Current conditions in elderly health promotion, Overall was at a high level, Desirable conditions in elderly health promotion, Overall was at the highest level. The index of needs of elderly health promotion was at 0.25, and the elderly have a need to promote their health by using music and dramatic arts to promote the health of the elderly, Overall was at the highest level. And the music and dramatic arts that was appropriate to promote the health of the elderly in Kalasin Province It is the Phu Thai Kalasin dance. (2) The program to promote the health of the elderly in Kalasin province using traditional music and dramatic arts consisted of 6 parts: Principles and rationale of the program. Purpose of the program The content of the program consists of promoting the health of the elderly by using traditional music and dance. Program structure and program activities and program evaluation, There was a suitable program to promote the health of the elderly in Kalasin province using traditional music and dramatic arts, Overall was at the highest level. and (3) The results of activities promoting the health of the elderly in Kalasin province using traditional music and dramatic arts. Overall was at the highest level. The results of promoting the health of the elderly in Kalasin province using traditional music and dramatic arts, After trying out the program Overall was at the highest level. and the results of the evaluation of satisfaction with the program to promote the health of the elderly in Kalasin province using traditional music and dramatic arts, Overall was at the highest level.